Mapping of Seawater Intrusion into Coastal Aquifer: A Case Study of Pekalongan Coastal Area in Central Java - Muhammad Irham Sahana; Roh Santoso Budi Waspodo (Journal of the Civil Engineering Forum, 2020)
Seawater intrusion promotes the degradation of groundwater quality through excessive pumping activities or natural phenomena such as tidal floods which are popular with coastal areas. Pekalongan city is one of the areas affected by this phenomenon and was analyzed in this study with reference to the 1986 Ad Hoc Sea Water Intrusion (PAHIAA) Decree which classifies water into five based on salinity. This involved using the Integrated Distance Method (IDW) to map and applying the logarithmic equation to determine the dispersion relationship. The results showed seawater intrusion has already affected groundwater quality up to 6.52 km from the coastline for total dissolved solids and electrical conductivity and 7.22 km for chloride ion.  The distribution of TDS, EC, and Cl- in the freshwater zone was also recorded to have reached 28.59 km2, 28.36 km2, and 23.95 km2 respectively. It is predicted that in 4 years, there would no longer be freshwater in Padukuhan Kraton Village due to decreasing groundwater quality caused by seawater intrusion. Furthermore, 23.03 km2 Pekalongan area which spread into 4.34 km2 to the West, 0 km2 to the South, 14.39 km2 to the North, and 1.28 km2 to the East of the district has also been affected and was discovered to be caused mainly by tidal flood from Bremi and Tirto rivers.